High-temperature thermomechanical treatment of hollow track pins of track-type machines - Zasypkin Andrei; Dement'yev Vyacheslav; Sterkhov Mikhail (MATEC Web of Conferences, 2017)
Very often the track pins of heavy-loaded track-type machines have insufficient fatigue safety margin, which causes their frequent breakage. One of the most rational solutions of the problem is the use of the high-temperature thermomechanical treatment of hot-rolled tubular billets for track pins. The analysis of the investigation results and engineering developments shows the possibility of improving the performance characteristic of hollow items (shafts, axis pins, track pins for a caterpillar mover, torsion suspensions of an undercarriage, etc.) by combining the thermomechanical treatment strengthening, various methods for improving the quality of the surface of tubular billets and the application of developed technological schemes in the factories producing tubular billets and items with diameter of Ø 10 ÷ 60 mm and the parameters of safety margin, precision and roughness required for the durability of the items.